2020
DOI: 10.1177/0971721820902964
|View full text |Cite
|
Sign up to set email alerts
|

Turning Straw to Gold: Mobilising Symmetry in Responsible Research and Innovation

Abstract: This article aims to reflect on the role of Science, Technology and Society (STS) research(ers) in co-constructing Responsible Research and Innovation (RRI) in the Global South. By reporting on RRI research in the Global South, here the Indo-Dutch NWO-MVI project on rice straw burning in Punjab, we make an argument for approaching RRI as a symmetric process of knowledge production mobilised by local actors and researchers alike. For STS researchers to responsibly engage with local innovation systems, their act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Our engagement in these politics led to moments of "disconcertement" with our own commitments toward what Responsible Innovation is and how it ought be put into practice, moments in which "the metaphysical commitments that lurk unacknowledged in your very person as a modern knower of the social come suddenly into the foreground revealing themselves as assumptions with no possibility of warrant" (Verran and Christie 2013, 53). Although further methodological exploration of the tensions of STS in policy settings, for example, through autoethnography (Law 2004), is beyond the scope of this paper, we suggest that remaining methodologically symmetrical in our analysis-despite, or maybe particularly because of STS's deep entanglement with participatory STI policy-is a first step toward responsible STS research and engagement (Mamidipudi and Frahm 2020).…”
Section: Methods Materials and Empirical Challengesmentioning
confidence: 98%
“…Our engagement in these politics led to moments of "disconcertement" with our own commitments toward what Responsible Innovation is and how it ought be put into practice, moments in which "the metaphysical commitments that lurk unacknowledged in your very person as a modern knower of the social come suddenly into the foreground revealing themselves as assumptions with no possibility of warrant" (Verran and Christie 2013, 53). Although further methodological exploration of the tensions of STS in policy settings, for example, through autoethnography (Law 2004), is beyond the scope of this paper, we suggest that remaining methodologically symmetrical in our analysis-despite, or maybe particularly because of STS's deep entanglement with participatory STI policy-is a first step toward responsible STS research and engagement (Mamidipudi and Frahm 2020).…”
Section: Methods Materials and Empirical Challengesmentioning
confidence: 98%
“…This provides opportunities for STEM scholars to address societal concerns before wide public controversy ensues. Such research practices could include community-led innovation (Liboiron 2017 , 2021 ), deliberative engagement in innovation (Wilsdon and Willis 2004 ), critical technology assessment (CTA) (Schot and Rip 1997 ; see also Barben et al 2008 ), and responsible innovation (Bronson 2019 ; Guston et al 2014 ; Mamidipudi and Frahm 2020 ; Owen et al 2013 ; Stilgoe et al 2013 ; von Schomberg 2011 ). Suggestions on how to improve funding policies and research practices.…”
Section: What Do Social Scientists Contribute To Science and Technolo...mentioning
confidence: 99%
“…Second, studies in STS have shown that different arenas have different norms for relevance and validity of knowledge (Mamidipudi and Frahm 2020;Valkenburg et al 2019). Thus, for biofuel policies to make sense to diverse stakeholders, it becomes crucial to understand how different groups mobilize available ideational and material resources to confront, challenge and negotiate with dominant knowledge claims inherent in such policies.…”
Section: Policy-relevant Sts: Rethinking Knowledge Expertise and Public Participationmentioning
confidence: 99%
“…In addition, the problem is not only that farmers' knowledge is poorly included into policy and technology development. It is also that their knowledge is considered through the lens of experts and policymakers, which already forms a straitjacket by which important cognitive capital is lost (Mamidipudi and Frahm 2020;Valkenburg et al 2019). A lack of attention to these other knowledges and practices will prevent any policy from working.…”
Section: Mobilizing Discourse Coalitions For Inclusive Policy-makingmentioning
confidence: 99%